2021
DOI: 10.1186/s12958-021-00720-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of erectile dysfunction, psychological disorders, and sexual performance in primary vs. secondary infertility men

Abstract: Background Many infertile couples might experience erectile dysfunction (ED) and significant changes in the quality of sexual life and psychological state though information is limited in secondary infertile men in China. To determine whether primary or secondary infertility is associated with ED, psychological disorders, and sexual performance. Methods This was a cross-sectional survey conducted at the Dongzhimen Hospital of Beijing University of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
3
8
0
1
Order By: Relevance
“…Wu et al investigated the anxiety status of infertile patients and the influential factors; they reported an anxiety prevalence of 61.4% in 306 infertile patients from the central‐south region of China (Wu et al, 2015). Ma et al also conducted a cross‐sectional survey in China and the anxiety trait of the participants was assessed using the GAD‐7 scale; their study revealed that the overall prevalence rate of anxiety (including mild generalized anxiety symptoms) was 60.7% in infertile men (Ma et al, 2021). Therefore, the relatively high prevalence of anxiety among the infertile men in our study is consistent with that in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al investigated the anxiety status of infertile patients and the influential factors; they reported an anxiety prevalence of 61.4% in 306 infertile patients from the central‐south region of China (Wu et al, 2015). Ma et al also conducted a cross‐sectional survey in China and the anxiety trait of the participants was assessed using the GAD‐7 scale; their study revealed that the overall prevalence rate of anxiety (including mild generalized anxiety symptoms) was 60.7% in infertile men (Ma et al, 2021). Therefore, the relatively high prevalence of anxiety among the infertile men in our study is consistent with that in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, male IIEF overall scores were higher in primary vs. secondary infertility (2 studies, 297 primary vs. 160 secondary infertility; MD 1.93, 95% CI 1.09, 2.76, Supplementary Figure S1). Furthermore, the prevalence of ED was higher, while libido, intercourse frequency and sexual satisfaction were lower, in men with secondary infertility (Ma et al, 2021, Sahin et al, 2017.…”
Section: Duration Of Infertility Primary and Secondary Infertilitymentioning
confidence: 94%
“…При этом в данном исследовании возраст, уровень образования и уровень дохода не оказывали значительного влияния на психологическое состояние, в то время как основными факторами риска ухудшения психологического состояния являлись:  продолжительность бесплодия: риск тревожных расстройств возрастал в 3,94 раза (p<0,02);  наличие сопутствующих заболеваний мужских половых органов (варикоцеле, эректильная и/или эякуляторная дисфункция): риск депрессии возрастал на 47%, а риск комбинации тревожных и депрессивных симптомов увеличивался на 56% (p<0,001) [19]. В исследовании Ma-Jianxiong et al (2021) установлено, что эректильная дисфункция достоверно чаще встречается среди мужчин с первичным бесплодием, приводит к выраженному снижению качества сексуальной жизни и к ухудшению психологического состояния [20].…”
Section: особенности переживания бесплодия у мужчинunclassified